Analisis Kebutuhan Pengembangan Modul TGT untuk Pembelajaran Relasi dan Karakter Kerja Sama Siswa - Kurniasih, Dian; Paridjo, Paridjo; Munadi, Munadi (Universitas Nusantara PGRI Kediri, 2026)
This study was conducted to identify the factors needed to design a Teams Games Tournament model-based teaching module focused on Relationship learning, with the hope of improving student learning outcomes and cooperative character. The study was conducted at SMP Negeri 5 Randudongkal during the 2024/2025 academic year. The research subjects included all 159 eighth-grade students, consisting of five classes: VIII A, B, C, and D with 32 students each, and VIII E with 31 students. Sampling was carried out using simple random sampling and resulted in two classes as respondents, namely VIII D as the control group and VIII E as the treatment group. The study method used was the first stage development of a qualitative descriptive approach. Data collection techniques included direct observation, distributing questionnaires to students, and interviews with teachers. The data obtained were analyzed using a qualitative descriptive approach and simple statistics. The results of the analysis showed that students needed teaching materials that were interesting, participatory, and supported group interactions. Teachers also expressed the need for modules that were structured, relevant to the context of students' lives, and able to foster positive character values. Based on these findings, the development of a module with a Teams Games Tournament approach is considered very necessary to support the quality of learning.